Changes in creatine transporter function during cardiac maturation in the rat. - Fischer, A; Ten Hove, M; Sebag-Montefiore, L; Wagner, H; Clarke, K; Watkins, H; Lygate, C; Neubauer, S (BioMed Central, 2010)
BACKGROUND: It is well established that the immature myocardium preferentially utilises non-oxidative energy-generating pathways. It exhibits low energy-transfer capacity via the creatine kinase (CK) shuttle, reflected in phosphocreatine (PCr), total creatine and CK levels that are much lower than those of adult myocardium. The mechanisms leading to gradually increasing energy transfer capacity during maturation are poorly understood. Creatine is not synthesised in the heart, but taken up exclusively by the action of the creatine transporter protein (CrT). To determine whether this transporter is ontogenically regulated, the present study serially examined CrT gene expression pattern, together with creatine uptake kinetics and resulting myocardial creatine levels, in rats over the first 80 days of age. RESULTS: Rats were studied during the late prenatal period (-2 days before birth) and 7, 13, 21, 33, 50 and 80 days after birth. Activity of cardiac citrate synthase, creatine kinase and its isoenzymes as well as lactate dehydrogenase (LDH) and its isoenzymes demonstrated the well-described shift from anaerobic towards aerobic metabolism. mRNA levels of CrT in the foetal rat hearts, as determined by real-time PCR, were about 30% of the mRNA levels in the adult rat heart and gradually increased during development. Creatine uptake in isolated perfused rat hearts increased significantly from 3.0 nmol/min/gww at 13 days old to 4.9 nmol/min/gww in 80 day old rats. Accordingly, total creatine content in hearts, measured by HPLC, increased steadily during maturation (30 nmol/mg protein (-2 days) vs 87 nmol/mg protein (80 days)), and correlated closely with CrT gene expression. CONCLUSIONS: The maturation-dependant alterations of CK and LDH isoenzyme activities and of mitochondrial oxidative capacity were paralleled by a progressive increase of CrT expression, creatine uptake kinetics and creatine content in the heart.